Effects of acute exercise on plasma erythropoietin levels in trained runners - Bodary, P. F.; Pate, R. R.; Wu, Q. F.; McMillan, G. S. (Medicine & Science in Sports & Exercise, 1999)
The results indicate that intermittent high intensity exercise does not have a significant effect on [EPO] in trained distance runners.